Freedom of Speech under the International Law - Kirilenko, Viktor; Alekseev, Georgy (Research Papers, 2018)
Freedom of speech determines the level of democracy development, as a political and legal principle of state organization. Realization of free speech is aimed at identifying the problems associated with the fourth industrial revolution and the introduction of elements of artificial intelligence into the national economy. The hypothesis was that all the states were largely unable to guarantee the protection of citizens from economic discrimination. The methodology of poliparadigmal analysis of the problems of free speech realization allows us to highlight contradictions between the norms established in international documents and the practice of public relations.
Keywords: Artificial intelligence; Copyright; Justice; Human rights